Analisis Penerapan Activity Based Costing Dalam Penentuan Harga Pokok Produksi - Destalya Adrian Nova, Gitta; Feblin, Anis; Annisa Prestajuly, Rahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2024)
This research aimed to analyze and compare the determination of the basic price of fried tofu production based on the traditional cost system with the Activity Based Costing system. The research analysis technique used was a qualitative descriptive analysis method, namely observation, interviews, documentation and information obtained from the factory through calculations. The research results showed that the calculation of the cost of production based on the traditional method. The difference that occured between the cost of production using the traditional cost system and the Activity Based Costing system was due to the imposition of factory overhead costs on each product. In the traditional cost system used, factory overhead costs were only charged to one cost driver. Meanwhile, in the Activity Based Costing system, factory overhead costs for each product were charged to many cost drivers according to the activities carried out in making fried tofu. So that the Activity Based Costing system was able to allocate activity costs to each product more accurately based on the consumption of each activity. However, the Activity Based Costing system had advantages compared to traditional cost systems. Although the traditional cost system was easier to implement because it only added up raw material costs, direct labor costs and factory overhead costs. However, this calculation was not appropriate for calculating the cost of production because it did not show the complete and accurate consumption of resources used in the production process.